KONTRIBUSI KEIKUTSERTAAN EKSTRAKURIKULER ROHANI ISLAM TERHADAP PERILAKU RELIGIUS PESERTA DIDIK SMA NEGERI 2 UNGARAN - Nurul Azimah; Rina Priarni; Ida Zahara Adibah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Moral and religious formation among senior high school students requires learning spaces that connect Islamic knowledge with daily practice. This study examines student participation in Rohani Islam (Rohis) Ad-Dakwah extracurricular activities and its contribution to the religious behavior of students at SMA Negeri 2 Ungaran. The study used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving the Islamic Education teacher as Rohis supervisor, the Rohis leader, and several Rohis members. Data analysis followed the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that student participation in Rohis was relatively high, reflected in active involvement in mentoring, Qur’an reading and writing programs, regular Islamic studies, hadrah practice, Islamic holiday programs, social activities, and religious habituation at school. Rohis contributed to better religious behavior through stronger prayer discipline, more frequent Qur’an recitation, improved manners, higher responsibility, social care, and more selective peer interaction. Rohis also acted as a practical laboratory for Islamic Education lessons, since students practiced religious values through organization, worship, and social interaction. The study indicates that Rohis has a meaningful role in strengthening religious culture and building students’ religious character in the school environment.